The emerging roles and mechanism of N6-methyladenosine (m6A) modifications in urologic tumours progression - Zhu, Wenhao; Zhao, Renshan; Guan, Xiaomin; Wang, Xu (Frontiers in Pharmacology, 2023)
Prostate cancer (PCa), bladder cancer (BC), and renal cell cancer (RCC) are the most common urologic tumours in males. N6-methyladenosine (m6A), adenosine N6 methylation, is the most prevalent RNA modification in mammals. Increasing evidence suggests that m6A plays a crucial role in cancer development. In this review, we comprehensively analyzed the influence of m6A methylation on Prostate cancer, bladder cancer, and renal cell cancer and the relationship between the expression of relevant regulatory factors and their development and occurrence, which provides new insights and approaches for the early clinical diagnosis and targeted therapy of urologic malignancies.